Information source, age and educational level as determinants of tourism destination image in Terengganu / Rose Aitul Adilah Mohamad Zaki - Mohamad Zaki, Rose Aitul Adilah (2010)
Image has been shown to be an important influence in the selection of vacation destinations. A model that represents the important determinants of destination image formation is developed based on previous studies. Directing promotional efforts to differed types of destinations within specific information usage in tourist destination selection remains a serious challenge for Destination Marketing Organization (DMO). Terengganu is a place where a lots of tourism destinations can be found such as emerald islands, impressive coastline, tropical rainforests, dazzling waterfalls, flora and faunas of exotic species, other natural wonders, tradition and heritage. Despite having a lot of tourism destinations, Terengganu still inability to draw much more international tourists. This is due to lack of maintenance of tourism image, continued follow-up plans and the selection of the types of information used by governments and private sectors to draw international tourist to travel in Terengganu. In respond to this, the purposes of this study is conducted to examine the role of information source usage and socio-demographic on the facet of destination image in Terengganu. The study seeks to address this by employing data in which was drawn from international via self-completed questionnaire at Sultan Mahmud’s airport, Kuala Terengganu’s city and Kapas’s island. The data was collected and analyzed by using the statistical package for the social sciences (SPSS) 17. According to findings, both of the types of information sources usage and age of respondents did not influence the cognitive components of destination image in Terengganu. The results of this study also highlighted that educational background of respondents significantly contributed to the cognitive components of destination image in Terengganu but not affected to the affective components of destination image. The results of this study offer several implications emphasizing on two major contributions, namely, theoretical and practical implications. In theoretical implications, the study basically enriched the body of literature by providing further insight on the facet of destination image especially the types of information source usage. In practical implication, this study also provides the insight to private sectors and marketers to promote their destination as many information channels as possible in order to draw a million of international tourist to go for a vacation in Terengganu.